2021
DOI: 10.1007/s11258-021-01134-4
|View full text |Cite
|
Sign up to set email alerts
|

Seed bank dynamics of the annual halophyte Salicornia ramosissima: towards a sustainable exploitation of its wild populations

Abstract: Halophytes are able to survive in the high salted areas of the world, and have been recognized as sources of bioactive metabolites. There is a need to design sustainable strategies for the use of wild populations of halophytic species in order to avoid irrational gathering. Seed banks are essential for resilience and regeneration in salty ecosystems. We sampled annual seed production, aerial and soil seed banks and seed dynamics for a year in four wild populations of the annual halophyte Salicornia ramosissima… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Therefore, this temporal pattern of germination may allow some S. ramosissima plants to avoid catastrophic events, such as herbivory or violent river floods, that could impact its populations throughout the growing season. Even so, the S. ramosissima seed bank was drastically reduced during the first year after seed dispersal [8], as occurred in S. europaea [19]. Additionally, all study populations presented similar plant height that was unrelated to plant density, so it seems to be linked to particular habitat characteristics or/and genetic differentiation, as demonstrated in S. europaea using transplant experiments [23,27,32].…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…Therefore, this temporal pattern of germination may allow some S. ramosissima plants to avoid catastrophic events, such as herbivory or violent river floods, that could impact its populations throughout the growing season. Even so, the S. ramosissima seed bank was drastically reduced during the first year after seed dispersal [8], as occurred in S. europaea [19]. Additionally, all study populations presented similar plant height that was unrelated to plant density, so it seems to be linked to particular habitat characteristics or/and genetic differentiation, as demonstrated in S. europaea using transplant experiments [23,27,32].…”
Section: Discussionmentioning
confidence: 77%
“…In contrast, S. ramosissima populations colonizing frequently waterlogged depressed zones presented five-times greater soil-seedbank densities and maximum plant densities (between 1257 and 51,558 plants m −2 ) than populations in elevated zones. These high seed-bank densities may be the result of higher in situ seed production [8] and the transport of seeds from elevated to depressed zones. Previous studies have reported a positive correlation between soil-seed-bank density and plant density for S. ramosissima [8] and S. europaea [19].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations